THE IMPACT OF URBAN HOUSING ON NATION BUILDING: MINNA IN PERSPECTIVE - Abubakar, Adamu; Umaru, Kuso; Bala, Adamu; Maigida, Jafaru; David, Shidali Samuel (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2019)
This study assessed the relationship between housing condition and the deterioration of urban physical environmental condition with physical planning variables in Minna town using three residential zones of varying Housing conditions and the intensity of Physical Planning. The data for this study was based on field survey and questionnaire designed to capture the physical environmental condition of housing reflected in density of occupancy, availability of water, sanitation facilities, vehicular accessibility etc, including other physical planning variables such as layout design of the settlements’ building subjected to approve plans and availability of infrastructures. A review of the operation of the Government agency responsible for physical planning and control also yielded significant information. The study indicates that the higher the housing density in the studied area, the lower the intensity of physical planning control and vice versa. Also, the higher the housing density, the higher the deterioration of the physical environment. The study concludes that there is a need for comprehensive research on the issue in order to establish an effective and sustainable intervention for nation-building.